PENGARUH PERUBAHAN IKLIM TERHADAP OPTIMASI KETERSEDIAAN AIR DI DAERAH IRIGASI GOLEK KECAMATAN PAKISAJI KABUPATEN MALANG DENGAN MEMPERGUNAKAN PROGRAM LINIER - Serang, Rudi (Fakultas Teknik, Universitas Brawijaya, 2012)
Global climatechangeaffects to temperature, relativehumidity, solarradiationlength, wind speed, rainfall andriverdischarge. Due to climatechangethe high of rainfallintensity impact onriver dischargefluctuationsin the wet anddry season. Floods anddroughtsas anatural eventaremoreoften occurredat this time. Golek kananIrrigationareahas a117hectares command area consistingofthefourtertiary those are 5hectares Karangdurentertiary, 100hectaresSutojayantertiary, 10hectaresPakisajitertiaryand2 hectares Glanggangtertiary, thereforetodeal with that extremeimpact,required a systematically irrigationmanagement plansin order tobe still profitable, especially for farmers.The methodology usedin the analysis ofirrigation water availability optimization at Golek kanan command area using theSimplexLinearProgrammingthatwill be obtained cropping area (A), discharge (Q)andmaximum benefit of agricultural production.Based on theanalysisresults indicatesthat has occurred the climate changeonGolek kanancommand area in 2001 that is markedbya shifted inthe rainyanddryseasonsand increasedthe amount ofannualrainfall. Increasing the amount ofrainfallhas an impactonthevolume availability of water intakechanges,before the climate change, the volume availability of water intheintake(cropping season) are MTI =706000 m3, MTII = 686000 m3andMTIII =764000 m3. While from thestudy resultalsoshowedthatafter theoccurrence ofclimatechange, volume ofwater availablein theintakeareMTI =1420000 m3, MTII = 690000 m3andMTIII =570000 m3. Volumeof water availability fromtheoptimizationofthe existing cropping pattern atGolek kananboth beforeand afterclimatechangeis stillsufficient to water requirement for everycropping seasonandthe difference inprofitis 98.525.000 rupiahs peryearwhichis obtainedfromagricultural production.Keywords: Climate Change, WaterAvailability, Linear Programming.